Case Report: Surgical Intervention Under Pheochromocytoma Multisystem Crisis: Timing and Approach - Luo, Shengjun; Cui, Qingao; Wang, Delin (Frontiers in Oncology, 2022)
Background: Progressive multiple organ failures still occur in some patients with pheochromocytoma multisystem crisis (PMC) despite α- and β-blockade are used, and emergency adrenalectomy may lead to rapid haemodynamic stabilization and recovery. Therefore, the optimal timing and surgical approach under PMC remain controversial. Case presentation: A 50-year-old man presented with persistent chest pain accompanied by vomiting and headache. CT showed a right adrenal mass, and plasma catecholamine levels were significantly elevated. Phenoxybenzamine was used, but his symptoms were aggravated. He progressed to acute respiratory distress syndrome (ARDS) and received mechanical ventilation. Reexamination CT showed pheochromocytoma rupture. Emergency pheochromocytoma resection was performed on the 5th day and he was discharged on 21th day. A 46-year-old female was admitted for intrauterine device removal and received hysteroscopy under intravenous anaesthesia. She presented with dyspnoea, fluctuating blood pressure and loss of consciousness 9 hours after hysteroscopy surgery. CT showed a left adrenal mass and plasma catecholamine levels were significantly elevated. Her condition fluctuated and could not meet the preoperative preparation criteria for pheochromocytoma despite adequate doses of α-blockade and β-blockade were taken. Furthermore, her lungs worsened due to recurrent crisis and pulmonary oedema. After multidisciplinary discussions, a laparoscopic left adrenalectomy with VA-ECMO support was performed on the 28th day, and she was discharged on the 69th day. Conclusion: Elective surgical resection is the essential therapy for PMC with adequate preoperative medical management. Emergency surgery is recommended for patients who fail to achieve medical stabilization or progressive organ dysfunction within 1 week, especially those with tumour rupture and uncontrolled bleeding. The laparoscopic approach may represent an option even under PMC.